Interactive Multimedia to Learn Reading Geguritan of XI Graders (Universitas Negeri Semarang, 2018)
Learning to read Geguritan needs joyful situation, adjusted level of skill and competence of the students, creativity and re-creativity using interactive learning media. The purpose of the study is to describe the needs and the effectiveness of the use of interactive learning multimedia in learning Geguritan reading. This R & D research uses data such as the analysis of necessity test, validity, and media effectiveness shows the development of interactive multimedia to learn Geguritan reading of the IX graders is learning media needed. The trial test shows the development of interactive learning media to learn it is effectively used to improve Geguritan reading skill.